Effects of a mealworm larvae-based diet on laying performance and egg quality in laying hens - Kaddour, A.; Diaw, M. T.; Saidj, D.; Yahi, K.; Moula, N. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
Soybean meal, the cornerstone of poultry nutrition, is increasingly scrutinized due to its heavy reliance on imported and genetically modified (GMO) crops, raising concerns about sustainability, cost, and compatibility with organic production systems. This challenge has spurred the search for al-ternative protein sources, with insect meals emerging as a promising solution. Among them, the yellow mealworm (Tenebrio molitor) offers a nutrient-dense, environmentally sustainable feed ingredient rich in proteins, lipids, and bioactive compounds. This study investigated the effects of dietary inclusion of T. molitor larvae on the performance and egg quality of laying hens. Thirty-six Isa-Brown hens (40 weeks old) were assigned to four dietary treatments: a control diet and diets supplemented with 1%, 2%, or 4% mealworm larvae (TM1, TM2, TM4). Over a four-week period, laying rate, feed conversion ratio (FCR), and egg quality traits (physical parameters, shell integrity, yolk cholesterol, and fatty acid composition) were measured. Results revealed that while laying performance remained unaffected (P = 0.48), hens in the TM4 group achieved significantly improved FCR (P = 0.03). Importantly, no adverse effects were observed on egg weight, shell quality, or nutritional composition. These findings demon-strate that moderate supplementation with T. molitor can enhance feed efficiency while maintaining egg quality, positioning insect proteins as a viable pathway toward more sustainable and resilient poul-try production.